ANALISIS TENAGA KERJA SEKTORAL DI KOTA TOMOHON - Christiawan A. Sengka; Juliana R. Mandei; Lyndon R.J. Pangemanan; Maya H. Montolalu (Universitas Sam Ratulangi, 2015)
ABSTRACT CHRYSTIAWAN ADJIE SENGKA. Labor Sectoral Analysis At Tomohon. Under the guidance (Juliana R. Mandei as Chairman, Lyndon R. J. Pangemanan and Maya H. Montolalu as Members.) This study aims to determine the growth rate of the labor sector and to determine the relation between economic growth (GDP) and employment rates to Tomohon. This research wasconducted for four months from December 2014 to March 2015 in Tomohon. In this study, the data used is secondary data obtained from the relevant agencies, namely the office of the Central Statistics Agency in Tomohon. The data is processed using descriptive analysis and presented in the from of tables and graphs. These result indicate that the potential sectors listed in Tomohon are very good in supporting regional economic growth and the growth rate of labor. More specifically in the services sector in Tomohon which has very high potential in employment. The growth rate of labor in Tomohon in 5-year period (2009-2013) has increased. In percentage of labor force growth rate and percentage rate of economic growth (GDP) each year for 5 years from 2009-2013 employment growth rate amounted to 10,17 percent, while the rate of economic growth (GDP) amounted to 10,02 percent. It can be seen that employment elasticity of 1,01 in which the figure is greater than 1 (>1), means that if the amount of GDP increased 1 %, the number of workers absorbed is equal to 1,01 %. Thus, is a relation between economic growth (GDP) and employment. Keyword : Labor and Economic sectors